Evidence of Criminal Acts in the Field of Electronic Information and Transactions in Review of Law No. 19 of 2016 concerning Electronic Information and Transactions - Sidabutar, Alcapon; Risdalina, Risdalina; Kumalasari M, Indra (International Journal Labs, 2024)
Advances in information technology have increased the number of crimes related to electronic transactions in Indonesia. Electronic evidence plays an important role in legal proceedings but often faces challenges in proving it. Law Number 19 of 2016 concerning Electronic Information and Transactions (ITE) establishes the legal framework for electronic evidence. This research aims to explore evidence of crime in information and electronic transactions according to the provisions of Law Number 19 of 2016 concerning ITE. This study uses a normative legal research method with a doctrinal approach. Secondary data are collected from relevant legal literature and analyzed to understand the application of legal doctrine related to electronic evidence. The results of the study show that electronic evidence such as electronic information, electronic documents, and printed documents are recognized as valid evidence based on Article 5 of the ITE Law. Proving criminal acts in the field of information and electronic transactions refers to Article 184 of the Criminal Procedure Code (KUHAP) which includes witness testimony, expert testimony, letters, instructions, and statements of the defendant. This research has implications for the importance of electronic evidence recognition in the Indonesian criminal justice system to increase the effectiveness of law enforcement in the digital era. These findings can be a reference for legal practitioners and policymakers in improving legal procedures related to electronic evidence.